Bioethics: a new frontier of biological science - Singh, A. K.; Singh, S.; Singh, M. P. (Cellular and Molecular Biology, 2012)
New researches in the field of biological sciences are creating new problems which were hitherto not faced. New techniques in biotechnology have paved way for transplantation for kidney, heart and liver successfully. In vitro fertilization, surrogate mothership, researches in totipotent stem cells which are capable of cloning are creating moral dilemma for the scientists. These techniques have immense capacity for the wellness of human beings. But there is every possibility of their misuse. Should researches in biotechnology be allowed unconditionally or there be some guiding principles? If the technique of cloning is perfected what will be the fate of the society which is based on conjugal love and trust? Should abortion and euthanasia be allowed? These questions need a clear answer. Here comes the role of bioethics to deal with such queries. In our view no such laws can be framed which can guide scientists in each and every case. Each case is specific and requires particular attention. There should be some norms for individual decision taker which are given in spiritual book of Hindu ‘ShrimadBhagavataGeeta'. With the help of this technique of decision making specific cases can be dealt with.